Tanggung Gugat Terhadap Kerugian Yang Diterbitkan oleh Anak di Sekolah Berdasarkan Pasal 1367 KUHPerdata: Tanggung Gungat, Kerugian, Pasal 1367 KUHPerdata. - Darmiwati Darmiwati2021 (Fakultas Hukum Universitas Islam Indragiri, 2021)
Schools as institutions that provide formal education play a very important role in producing quality generations, both cognitively and effectively. In school life, students do not rule out dealing with legal problems because of the harmful actions they do inside and outside school. detrimental acts are regulated in Article 1365 of the Civil Code which reads that